The left-handed curriculum creative experiences for empowering teachers - McDermott McNulty, Morna (Emerald Publishing Limited : Information Age Publishing, 2013)
Teaching is not merely a technical process- it is one that requires creative and inspirational thinking, not only on the part of students but for teachers themselves as artful, reflective beings. The purpose of this book is to provide educators with creative experiences which unlock their imaginative potential so they can re-envision their curriculum to promote active learning, culturally relevant pedagogy, and differentiated instruction. This book guides the reader through a series of experiences intended to tap into the right side of the brain, and provide educators opportunities to re-imagine their existing curriculum in new ways. Through this re-imaging (or re-envisioning) of the creative potential within themselves, teachers can redesign their curricula in ways that best meet the needs of their learners, schools, and communities. This book emphasizes creativity in teaching as a collaborative effort. The experiences and ideas presented in this book are intended to inspire small groups or whole communities (including schools) to work together and support each other in their creative efforts. Creativity does not just exist for individuals in isolated contemplation but resides instead in the relational work that community members create together toward a shared vision. In order to encourage imaginative students who will have the capacities to see the world, not merely as it is, but as it could be, we need to encourage teachers to tap into their creative imaginative capacities to teach as well. Such work cannot be performed in isolation. Creative social change requires that we imagine together that which we cannot do alone.